Association of envelope-specific B-cell differentiation and viral selective pressure signatures in HIV-1 CRF01_AE infection - Hau, Trang Thi Thu; Nishizawa, Masako; Harada, Shigeyoshi; Phan, My Ha; Kanno, Yoshiaki; Nomura, Takushi; Matsuoka, Saori; Kawana-Tachikawa, Ai; Hall, William W.; Matano, Tetsuro; Nguyen, Lan Anh Thi; Yamamoto, Hiroyuki (AIDS (London), 2022)
In HIV type 1 (HIV-1) infection, virus-specific B-cell and neutralizing antibody (NAb) responses are impaired but exert selective pressure on target viral Envelope (Env) resulting in prominent sequence diversification among geographical areas. The basal induction patterns of HIV Env-specific B cells and their interaction with HIV Env awaits clarification. We investigated the relationship of Env polymorphisms and Env-specific B-cell responses in treatment-naive HIV-1 CRF01_AE-infected Vietnamese. Samples of 43 HIV-1 CRF01_AE infection-identified individuals were divided into acute-phase ( n  = 12) and chronic-phase ( n  = 31) by combined criteria of serological recent-infection assay and clinical parameters. We quantified subcloning-based polymorphic residue site numbers in plasma-derived Env variable region 1-5 (V1-V5)-coding regions within each individual, designating their summation within each region as variant index. Peripheral blood Env gp 140-specific B-cell responses and plasma neutralizing activity of Env pseudoviruses were examined to analyze their relationship with variant index. HIV-1 CRF01_AE Env gp140-specific total B-cell and plasma cell (CD19 + IgD - CD27 + CD38 + CD138 + ) responses were determined. In chronic-phase samples, significant correlation of variant index in all Env V1-V5 regions with Env-specific plasma cell responses was shown, and V1-V5 total variant index correlated stronger with Env-specific plasma cell as compared with total Env-specific B-cell responses. Env V5 variant index was significantly higher in chronic-phase cross-neutralizers of V5-polymorphic/VRC01-insensitive CRF01_AE Env. Results revealed the association between circulating Env-specific plasma cell responses and Env polymorphisms, implicating selective pressure on Env by plasma cell-derived antibodies and conversely suggests that Env-specific B-cell induction alone is insufficient for exerting Env selective pressure in HIV infection.